Studi Fenomenologi Tentang Ungkapan Makna Dalam Sebuah Sorotan Kepatuhan Wajib Pajak Untuk Menunaikan Kewajiban Perpajakan - Rafles Ginting; Ardimansyah Ardimansyah; Rizky Firmansyah (Jurnal Akademi Akuntansi, 2022)
The purposes of this study were to determine the interpretation and compliance of SME taxpayers in Bengkulu city to tax obligations and differences of interpretation between the micro and small enterprises. The interpretation was assessed with a great understanding of the taxation of SME taxpayers and taxpayer compliance with tax obligation was measured by the SME taxpayer compliance in paying taxes every year. The research was conducted in the city of Bengkulu with interviews directly to six randomly selected informants. Informants were of micro and small business owners. The results of this study showed a good interpretation in the understanding of the tax informant, the informant has not obediently tax obligations, and there were differences in interpretation and compliance of SME taxpayers in tax obligation between the micro and small enterprises in the city of Bengkulu.